Monsoonal influence on floating marine litter pathways in the Bay of Bengal - Lianne C. Harrison; Jennifer A. Graham; Piyali Chowdhury; Tiago A. M. Silva; Danja P. Hoehn; Alakes Samanta; Kunal Chakraborty; Sudheer Joseph; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Ocean Science, 2025)
Marine litter in the Bay of Bengal has been under-studied despite large quantities of mismanaged waste reportedly entering the ocean from its surrounding countries. The seasonal reversal of monsoon currents in this region provides a unique environment for the transport of floating macro-litter. A particle tracking model is used here to investigate source-to-sink connectivity of marine debris between countries via oceanic pathways in the Bay of Bengal. We use an approach considering uniform release of particles along the entire coastline, avoiding the considerable uncertainties associated with assumed riverine sources. Two different simulations are considered, forced with either a high-resolution ocean hindcast developed specifically for the Bay of Bengal or a lower-resolution dataset which includes data assimilation. The vast majority of particles released during our simulations were found to beach within 16 months; most particles beached in their country of origin (57 %–90 %), with connectivity towards Myanmar accounting for the second highest connectivity rates (2 %–29 %) from many countries within the Bay of Bengal. This is likely due to the relatively large size of Myanmar's coastline and that it lies in the path of the East India Coastal Current for much of the year (February–September). Patterns of connectivity were found to change along with the monsoon and the post-monsoon period (October–January) showed a notably greater dispersal of particles than the rest of the year. Both simulations were evaluated using the pathways of undrogued surface drifters, which moved primarily within the open ocean, with better agreement found here for particles advected by data-assimilated ocean velocities. This study will therefore crucially inform future research and policy in this region, providing advice on the benefits and suitability of selecting different modelling approaches independent of assumptions of the source locations or volumes.